A Provincial University at the Times of the World Pandemic: Preservation or Development? - Mikhailov, Alexey; Burlakova, Mariia (International Dialogues on Education Journal, 2020)
The authors describe the issues a Russian provincial university has attempted to adjust during the Covid-19 pandemic, and the significant challenges as well as the opportunities that faculty members and students continue to encounter during these times of uncertainty.